SoK: Scalability Techniques for BFT Consensus - Berger, Christian; Schwarz-Rüsch, Signe; Vogel, Arne; Bleeke, Kai; Jehl, Leander; Reiser, Hans P.; Kapitza, Rüdiger (Proceedings of the 5th IEEE International Conference on Blockchain and Cryptocurrency, 2023)
With the advancement of blockchain systems, many recent research works have proposed distributed ledger technology (DLT) that employs Byzantine fault-tolerant (BFT) consensus protocols to decide which block to append next to the ledger. Notably, BFT consensus can offer high performance, energy efficiency, and provable correctness properties, and it is thus considered a promising building block for creating highly resilient and performant blockchain infrastructures. Yet, a major ongoing challenge is to make BFT consensus applicable to large-scale environments. A large body of recent work addresses this challenge by developing novel ideas to improve the scalability of BFT consensus, thus opening the path for a new generation of BFT protocols tailored to the needs of blockchain. In this survey, we create a systematization of knowledge about the novel scalability-enhancing techniques that state-of-the-art BFT consensus protocols use. For our comparison, we closely analyze the efforts, assumptions, and trade-offs these protocols make.<br
Keywords: Byzantine Fault Tolerance; Consensus; Scalability; Blockchain

SURESOFT: Towards Sustainable Research Software - Blech, Christopher; Dreyer, Nils; Friebel, Björn; R. Jacob, Christoph; Shamil Jassim, Mostafa; Jehl, Leander; Kapitza, Rüdiger; Krafczyk, Manfred; Kürner, Thomas; C. Langer, Sabine; Linxweiler, Jan; Mahhouk, Mohammad; et al. (2022)
Researchers develop software to process or generate data to test their scientific hypotheses. Especially researchers from STEM disciplines (Science, Technology, Engineering, and Mathematics) validate their models through self-developed software prototypes. However, they do not necessarily have a programming or software engineering background. Moreover, scientific software development happens in a time-constrained environment focusing on the fast publication of results. In addition, as scientists usually have limited contracts, the software is developed with short-term goals in mind. Therefore, the resulting software is mostly rapidly developed and contains code artifacts that are hard to maintain, extend and even reproduce due to missing documentation or dependencies. These factors, among others, hinder researchers from progressing and further developing their software. Thus, research software sustainability is vital to the research process to ensure that software can be evolved and reused by the next generation of scientists. To foster sustainability, scientists can highly benefit from education in principles and practices of software engineering, which can further be supported by established methods, tools, and technologies. This paper introduces SURESOFT, a twofold approach to address challenges in the development of research software regarding sustainable science that combines tools and infrastructure with education in the form of workshops and training. Furthermore, we report our experience of applying the SURESOFT approach to five software projects from different fields and discuss challenges, such as common bad practices and applicability in diverse scenarios. </